Contingency approach towards adoption of jomPAY in Malaysia - Obinna, Odimegwu Malachy; Zainol, Zaini; Mokhtar, Norsyahida (Globeedu Group India, 2018)
The need for full migration to e-payment system led to the introduction of JomPAY in Malaysia. JomPAY has been showing promising growth since its introduction but has a slow rate of adoption. Therefore, using the contingency theory concept, this study aims to examine those (internal cum external) factors influencing the adoption of JomPAY in Malaysia. The extant literature indicates that factors such as security, trust, self-efficacy, government support, socio cultural influence, and legal and regulatory framework influence the adoption of e-payment, which in this study focuses on JomPAY as an e-payment channel. A self-reporting questionnaire was developed and distributed to 210 respondents, with 149 valid response for the statistical analysis. From the empirical result which was achieved using SPSS, two out of the six hypotheses were rejected; H1 and H3, while the rest but government support were significant. Trust and socio cultural influence had a positive relationship with JomPAY adoption as expected. The use of contingency theory in this study might have limited the exploration of other factors that can influence JomPAY adoption. Therefore, there is an issue of generalization which can be addressed by future research. Also, future research can extend the stakeholders’ participation and not limit to only consumers for more comprehensibility of the factors influencing JomPAY. As the first study on JomPAY, this study has provided advanced knowledge on the current state of JomPAY in Malaysia. The factors which appear to be significant in this research will help the facility providers, policymakers and the developers to provide a better system to increase JomPAY adoption and use in Malaysia.